2013
DOI: 10.1128/jb.00911-13
|View full text |Cite
|
Sign up to set email alerts
|

Identification of SPOR Domain Amino Acids Important for Septal Localization, Peptidoglycan Binding, and a Disulfide Bond in the Cell Division Protein FtsN

Abstract: bSPOR domains are about 75 amino acids long and probably bind septal peptidoglycan during cell division. We mutagenized 33 amino acids with surface-exposed side chains in the SPOR domain from an Escherichia coli cell division protein named FtsN. The mutant SPOR domains were fused to Tat-targeted green fluorescent protein ( TT GFP) and tested for septal localization in live E. coli cells. Lesions at the following 5 residues reduced septal localization by a factor of 3 or more: Q251, S254, W283, R285, and I313. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
31
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 50 publications
5
31
0
Order By: Relevance
“…However, it is not yet possible to model the SPOR:PG complex to address issues such as whether the presence of stem peptides sterically blocks binding of the glycan chain to the protein. Mutagenesis of the SPOR domain from FtsN led to the unexpected discovery of a disulfide bond that is critical for the stability of the domain (51). Subsequently, Beckwith's group demonstrated that the disulfide is required for the overall stability of FtsN, so much so, in fact, that when an E. coli disulfide bond (dsb) mutant is grown anaerobically, FtsN is almost completely degraded and division fails (52).…”
Section: Spor Domains Exhibit An Rnp Fold and A Conserved Pg-binding mentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is not yet possible to model the SPOR:PG complex to address issues such as whether the presence of stem peptides sterically blocks binding of the glycan chain to the protein. Mutagenesis of the SPOR domain from FtsN led to the unexpected discovery of a disulfide bond that is critical for the stability of the domain (51). Subsequently, Beckwith's group demonstrated that the disulfide is required for the overall stability of FtsN, so much so, in fact, that when an E. coli disulfide bond (dsb) mutant is grown anaerobically, FtsN is almost completely degraded and division fails (52).…”
Section: Spor Domains Exhibit An Rnp Fold and A Conserved Pg-binding mentioning
confidence: 99%
“…The essential nature of FtsN=s disulfide had been overlooked in previous studies of dsb mutants because molecular oxygen and/or oxidized components of the growth medium allow sufficient disulfide bond formation during aerobic growth. About 15% of SPOR domains in the sequence databases have paired cysteines, suggesting that there is a widespread connection between cell division and redox metabolism (51).…”
Section: Spor Domains Exhibit An Rnp Fold and A Conserved Pg-binding mentioning
confidence: 99%
“…domains from DamX and FtsN that impair septal localization in vivo also impair PG binding in vitro, indicating that PG binding is necessary for septal localization (21,22). Nevertheless, it is not known whether PG binding is sufficient for septal localization or whether denuded glycans are enriched in septal PG.…”
mentioning
confidence: 98%
“…FtsN was identified as a multicopy suppressor of a conditional mutation in ftsA but suppresses conditional mutations in ftsI, ftsQ, or ftsK as well (29)(30)(31). FtsN has at least four functional domains: an N-terminal cytoplasmic domain (FtsN cyto ), which contains a conserved motif responsible for interaction with FtsA; a transmembrane domain; and two periplasmic domains, the E-domain (FtsN E ), which triggers septal PG synthesis, and a C-terminal SPOR (septal peptidoglycan binding) domain, which interacts with peptidoglycan strands denuded by amidases (12,27,28,(32)(33)(34)(35)(36). FtsN E was designated as the essential domain because it can…”
mentioning
confidence: 99%